Determination of health status perception and orthorexia nervosa tendencies of Turkish yoga practitioners: a cross-sectional descriptive study
As part of the yoga the possibility that excessive attention paid by practitioners to diet and food quality is expected. This study was aimed to determine health status perception and orthorexia nervosa tendencies of yoga practitioners. This cross-sectional descriptive study was conducted at three yoga centers in Izmir. The population of the study consisted of 153 people registered in yoga centers between March and May 2017. The data were collected using a personal information form (11 questions), Perception of Health Status Scale and Orthorexia Nervosa (Orto-11) Scale. While perceived physical health was “good” for 68.0% of the participants, the mean perceived health score was 1.94Å